Strategi Pemasaran Dengan Pendekatan Marketing Mix Batik Ayu Gestar Gedog, Kota Blitar - Rachma Yasin; Ahmada Rifqi Zulfahmi; Brilian Valentia Stevani; Ni Kadek Galuh Anjani; Nathania Grace Edwin; Fahira Nisa Aini; Mu’tasim Billah (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Batik, a culture of Indonesia and is a form of high-quality ancient art. Batik industry in Indonesia is usually in the form of Small and Medium Enterprises and has become some people’s livelihood. UNESCO’s acknowledgment of Batik as a world heritage has an impact on the increasing batik industry. One of the batik producers in Gedog, Sananwetan, Blitar City which is Batik ayu Gestar has some problems that slow down their business starting from production to promotional problems such as digital marketing. Therefore, this activity is an effort for Batik Ayu Gestar in order to understand the importance of digital marketing, marketing mix, and provide opportunities to be able to apply the marketing mix process based on consumer needs and wants through social media. This service activity is carried out as a Focus Group Discussion. The results obtained are partner empowerment through FGDs regarding digital marketing, consistency of brand identity, creation of an Instagram, education on price consistency before and after the pandemic, and coordinating collective production processes for groups. In conclusion, Batik Ayu Gestar can understand and implement marketing strategies with the 4P Marketing Mix approach in this digital era.